(A Message in Nile) For Ahmed هbn Imad ibn Yusuf al-Aqfhasi - Sundus Z. khalaf Al-Shugary ســندس زـيدان خــلف الشـجـيري (College of Education for Women, 2019)
Ahmed ibn Imad ibn Yusuf al-Aqfhasi (808 AH / 1405 AD) is a small message that speaks about the Nile River in all its sides, despite its limited papers, but it is one of the manuscripts of the important geographical literature for its geographical, historical, religious and grammatical information. it was not limited to the information of the author alore, but taken from many sources below, which added to the importance of the fact that it has saved us the names of the sources that preceded him in mentioning this river with the names of its authors.The method of the Aqfhasi was characterized by scientific methodology in writing and clarity, with reference to some of the myths that people carried in their minds about the Nile River at that time.